Company Size as Moderating Variable of Intellectual Capital and Good Corporate Governance Towards the Financial Performance of Banking Firms - Novitasari , I Gusti Ayu (Jurnal Penelitian dan Pengembangan Sains dan Humaniora, 2023)
The level of business competition is very dynamic, causing companies to take various ways to improve performances that can be viewed through financial statements. This study aims to analyze the company size as moderating variable for intellectual capital also good corporate governance after financial performance at banking firm at Indonesia Stock Exchange. This research was conducted on banking companies because banking is one of the most competitive industries and has an important influence on the economy. Research sample are banking companies listed on the Indonesia Stock Exchange from 2018 to 2021, reviewed via company annual reports. This paper examined Return on Assets (ROA), Value Added Intellectual Coefficient (VAICTM), GCG index and company size. The sampling method using a purposive sampling technique and a sample of 44 companies were counted. The data analysis technique uses SEM PLS. Based on the results of the analysis, value added intellectual coefficient and Good corporate governance give positive significant effect at financial performance meanwhile Company size  has no significant effect on the relationship between the value added intellectual coefficient and the financial performance and weakens the relationship between the influence of good corporate governance towards financial performances of banking companies on the Indonesia Stock Exchange. These implications can help companies maximize their financial performance in a competitive business environment.